Pencak Silat Aliran Sang Maung Bodas: Refleksi Etika, Spiritualitas, dan Identitas Budaya dalam Tradisi Sunda dan Pesantren - Yusep Saepulloh; Rudi Ripandi; Moch Mumin Amirulloh (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This study investigates the symbiosis between the practice of Pencak Silat Aliran Sang Maung Bodas and a holistic pedagogical framework known as the concept of ‘Five Of’ (To guard, to protect, to guard, to guard, to protect). This model, developed by the Dzikir Al-Fath Modern Islamic Boarding School, is intended to respond to contemporary challenges in the form of a crisis of moral integrity and the high rate of educated unemployment or